Comparative assessment of the contentof mobile phosphor usinvario usgenetic horizons of ordinary chernozem on tilled field compared with virgin soil in conditions of the northern Steppe of Ukraine - Крамарьов, С. М.; Крамарьов, О. С.; Писаренко, П. В.; Христенко, А. О.; Токмакова, Л. М.; Жученко, С. І.; Сироватко, В. А.; Сироватко, К. В. (Scientific Progress & Innovations, 2014)
The change of the content of mobile phosphorus in the genetic horizons of ordinary black plowing a relatively virgin land under North Steppe of Ukraine at different research methods has been analyzed. For accurate diagnosis of phosphate status of these soils should use one of three methods: Karpinski– Zamiatina (GATS 4727), Machygin (GATS 4114) or Olsen (GATS ISO 11263). It has been established that real natural security arable layer ordinary black phosphorus corresponds to the boundary of low and medium security that element of plant nutrition.